2023
DOI: 10.1037/pspi0000421
|View full text |Cite
|
Sign up to set email alerts
|

Does the follow-your-passions ideology cause greater academic and occupational gender disparities than other cultural ideologies?

Abstract: Five preregistered studies (N = 1934) demonstrate that the prevalent U.S. ideology to “follow your passions” perpetuates academic and occupational gender disparities compared to some other cultural ideologies. Study 1 shows that the follow-your-passions ideology is commonly used by U.S. students in making academic choices. Studies 2–5 find that making the follow-your-passions ideology salient causes greater academic and occupational gender disparities compared to the resources ideology (i.e., the idea that one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In contrast, female participants had lower intentions of pursuing STEM careers relative to male participants when a “follow your passion” ideology was indicated. The “follow your passion” ideology refers to the belief that “occupational choices should be determined by one’s strong interests, preferences, and positive feelings” (Siy et al, 2023, p. 2), which means that the perceived intrinsic value of a subject or occupation is more influential. As gender differences in intrinsic value have been observed repeatedly (e.g., Lazarides & Lauermann, 2019), including in the present study, another path to reducing gender differences may be to deemphasize this ideology and discuss other arguments for or against occupational options when advising youth (e.g., job security).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, female participants had lower intentions of pursuing STEM careers relative to male participants when a “follow your passion” ideology was indicated. The “follow your passion” ideology refers to the belief that “occupational choices should be determined by one’s strong interests, preferences, and positive feelings” (Siy et al, 2023, p. 2), which means that the perceived intrinsic value of a subject or occupation is more influential. As gender differences in intrinsic value have been observed repeatedly (e.g., Lazarides & Lauermann, 2019), including in the present study, another path to reducing gender differences may be to deemphasize this ideology and discuss other arguments for or against occupational options when advising youth (e.g., job security).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gender differences in intrinsic value may be particularly harmful when students believe that they should "follow their passion" in their career (Siy et al, 2023). Siy et al (2023) showed experimentally that when following a resource ideology that focuses on job security and income, male and female participants indicated equal (hypothetical) intentions of pursuing STEM careers. In contrast, female participants had lower intentions of pursuing STEM careers relative to male participants when a "follow your passion" ideology was indicated.…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…The current findings suggest that adolescence is a period characterized by changes in math ability stereotype beliefs and that individuals' more traditional beliefs may emerge by late adolescence and persist well into adulthood. Gender stereotypes about math, paired with cultural values that emphasize "following your passions", may result in adolescents relying on stereotypes to choose majors and careers, resulting in STEM gender gaps [61]. However, it is important to note that although math gender stereotypes moved toward being more traditional for all racial/ethnic groups, Black and Latina girls did not hold traditional stereotypes in late adolescence.…”
Section: The Prevalence and Changes In Gender Stereotypesmentioning
confidence: 99%